Development of vapor-liquid-liquid equilibria (VLLE) circulating still for the VLLE data measurement of acetone-toluene-water system with and without salt - Novianti, Dyah Setia (Animo Repository, 2007)
The growth of semiconductors, electronics and optical devices industries all over the world resulted in an increase in hazardous spent solvents. These spent solvents, such as isopropyl alcohol (IPA), acetone, toluene, methyl ethyl ketone (MEK), and n-methyl pyrolidone (NMP), are highly valuable. Therefore, their recovery into high purity solvents is needed to reduce operating costs and, at the same time, preserve the environment. However, most mixtures of these solvents form non-ideal systems in the presence of specific groups, particularly polar groups containing oxygen, nitrogen, chlorine, or fluorine, resulting in the formation of azeotropes. Heterogeneous azeotropic distillation with salt is one method that can facilitate the recovery of the solvents. The Vapor-Liquid-Liquid Equilibrium (VLLE) data is necessary to design distillation columns that will be used for the recovery. The VLLE apparatus, fabricated based on the design of Iwakabe and Kosuge (2001), which was modified to suit the system under study, was tested by generating binary vapor-liquid equilibrium (VLE) of ethanol-water system and comparing the obtained data with literature. Herington’s area test has confirmed the thermodynamic consistency of the obtained data. The VLLE data of ternary system acetone-toluene-water were determined using the fabricated apparatus with and without the salt effect. Sodium chloride (NaCl) and cupric chloride (CuCl2) at two salt concentrations, which are at saturated salt concentration of initial liquid mixtures and a half of it for NaCl, and for CuCl2 at 25% and 50% of saturated salt concentration of initial liquid mixtures; were employed to investigate the salt effect on the boiling point and VLLE of this ternary system. The effect of NaCl was found to be stronger thanCuCl2 in lowering the boiling point. On the vapor phase, the salting-in effect of toluene was observed in the presence of both salts, thus, more toluene was found in it. The higher concentration of both salts has the greater salting-in effect of toluene in the vapor phase. The salting-out effect, determined by decreasing solubility, of toluene has been observed in the aqueous phase and that of water in the organic phase in the presence of NaCl and CuCl2. Furthermore, more acetone, which is less polar than water was found in the organic phase. These effects cause the increasing area of the two-phase region on the ternary graph, the possibility of changing the type of the system from type 1 to type 2, and altering the ternary azeotrope point. At 50% of saturated concentration in the initial mixture, CuCl2 was observed to have larger effect than NaCl in altering the heterogeneous azeotrope point resulting to higher purity of acetone in this point. The salting in effect of acetone in the organic phase was also found to be larger in the presence of CuCl2 than NaCl at 50% saturated concentration of initial mixture resulting in a larger heterogeneous area. The UNIQUAC model was used to correlate the ternary experimental VLLE data of acetone-toluene-water without salt effect. The model did not represent the obtained data well, since the binary interaction parameters obtained from binary data cannot estimate the behavior of the ternary mixture accurately.